2020
DOI: 10.1177/0004867420954286
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of predictors and outcomes of community treatment orders in Australia and New Zealand

Abstract: Objectives: Australia and New Zealand have some of the highest rates of compulsory community treatment order use worldwide. There are also concerns that people from culturally and linguistically diverse backgrounds may have higher rates of community treatment orders. We therefore assessed the health service, clinical and psychosocial outcomes of compulsory community treatment and explored if culturally and linguistically diverse, indigenous status or other factors predicted community treatment orders. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 55 publications
1
37
1
Order By: Relevance
“…One example is the implementation of community treatment orders (CTOs), the use of which is increasing in several countries (Kisely et al . 2020). In jurisdictions such as England and New Zealand, nurses are now formally integrated in the CTOs’ enforcement process and may be designated as responsible clinicians (McKenna et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the implementation of community treatment orders (CTOs), the use of which is increasing in several countries (Kisely et al . 2020). In jurisdictions such as England and New Zealand, nurses are now formally integrated in the CTOs’ enforcement process and may be designated as responsible clinicians (McKenna et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although coercive practices within the psychiatric asylums of the past (Goffman 1961;Szasz 2009) have been decried and modified since that time (notably due to deinstitutionalization and the civil rights movement), coercion is still present in the psychiatric environment and community care. One example is the implementation of community treatment orders (CTOs), the use of which is increasing in several countries (Kisely et al 2020). In jurisdictions such as England and New Zealand, nurses are now formally integrated in the CTOs' enforcement process and may be designated as responsible clinicians (McKenna et al 2006;Veitch & Oates 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With more effective communication, clinicians could help reduce negative feelings towards LAI treatment for those treated under treatment orders. Despite the clinical relevance, the association between LAI use and treatment orders has not been sufficiently explored in Australasia (Kisely et al, 2020). Future research should explore in more detail how community treatment orders may impact on LAI treatment for our patients and clinicians, both in quantitative and qualitative manners.…”
Section: Lais Utilisation In People With Psychosismentioning
confidence: 99%
“…The rates of CTO use in Australia are high compared to other parts of the world but show a wide variation by jurisdiction (Light, 2019;Light et al, 2012;O'Donoghue et al, 2016;Rugkasa, 2016). For instance, the proportion of people in contact with state-run mental health services on CTOs ranges from 3.1% in Western Australia to 22.3% in Queensland (Kisely et al, 2020a(Kisely et al, , 2020b. A recent systematic review of CTO use across Australian and New Zealand found that CTO placement was associated with being male, single, a lack of vocational engagement, migrant background, primary diagnosis of non-affective psychosis, comorbid substance use and past contact with the criminal justice system (Kisely et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%